Meta, Meta, Meta: Modeling in a Methods Course for Teaching English - Jay, Joelle K. (Teacher education quarterly (Claremont, Calif.), 2002)
Examines the use of modeling techniques in a methods course to help prepare prospective English teachers, focusing on: demonstrations and explicit instruction, use of class assignments and explicit modeling, and ongoing modeling and reflective analysis. Each section contains a description of instruction and a description of student and instructor perspectives. (SM)